Challenges of Winter Tourism in Albania: A Review - Spahiu, Elton; Kushta, Entela (European Journal of Social Science Education and Research, 2023)
Albania is known for its unique and stunning natural beauty. Mountains and hills cover a large portion of the region, almost two-thirds of the total surface. The outstanding terrain, with its many cracks and microforms make this country an ideal setting for a variety of outdoor tourism activities, especially during the winter season attracting both domestic and foreign visitors. The current research aims at looking into some of the challenges that Albania’s booming winter tourism industry is facing. The first concern identified is scarce and sometimes completely absent infrastructure in remote mountainous areas, which strongly impacts accessibility and guest accommodation. Even though in some areas snow cover is above 100 days, seasonality is still another aspect that highlights the importance of diversifying tourism offer to attract tourists all year. Environmental issues pose a threat for the delicate alpine ecosystems, thus making the implementation of eco-friendly practices and laws for sustainable tourism a must. In addition, the review underscores the vital role of sustainable development, which balances economic growth with environmental preservation. Albania can develop a robust and profitable winter tourism sector by tackling these difficulties through joint efforts and the implementation of evidence-based policies, which will in turn benefit the country’s economy, biodiversity, and cultural heritage.